UPAYA MENINGKATKAN ILASIL BELAJAR PASSING ATAS BOLA VOLI MELALUI METODE LATIHAN OVERHEAD THROW PADA SISWA KELAS XL SMA YAPIM BIRU-BIRU TAHUN AJARAN 2017/2018 - Imam Mulmuttaqin (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
The purpose of this research is to improve the learning outcomes of passing over volleyball by using the Overhead Throw training method for students of class XI SMA YÁPIM BIRU-BIRU TA.2017/2018. To find out the results of this study the researchers used the classroom action method. To obtain the data in this study, a learning outcome test in the form of a portfolio was carried out and continued with the use of the Overhead Throw exercise method. After that, a test of learning outcomes was held in cycle I and cycle II in the form of the basic technique of passing over volleyball. Based on the results of the first cycle test conducted on XI grade students of SMA YAPIM BIRU-BIRU, from 30 students there were 16 students who achieved the mastery level of learning with an average score of 77.60 and students who did not reach the mastery level, namely 14 students with an average score of 66.50. . Then the researchers conducted a cycle II test on students who did not reach the level of completeness as many as 14 students, then the results obtained that the students had achieved the level of completeness and 3 students did not reach the level of completeness. The researcher concludes that learning using the Overhead Throw training method can improve the over-passing learning outcomes in volleyball games for XI SMA YAPIM BIRU-BIRU FY 2017/2018 students.